Judi Online dan Perilaku Sosial Remaja di Desa Kotasan Kecamatan Galang: Online Gambling and Social Behavior of Adolescents in Kotasan Village, Galang District - Taufik Rivaldi; Nuriza Dora (ITScience (Information Technology and Science), 2025)
This study examines the widespread phenomenon of online gambling among adolescents, including in rural areas, which has created quite complex social problems. This study aimed to describe the level of adolescent involvement in online gambling, its impact on social behavior, and family and community efforts to prevent it in Kotasan Village, Galang District. The study used a qualitative descriptive method with primary informants (village officials and community leaders), key informants (adolescent online gamblers), and supporting informants (peers and community members). Data were obtained through in-depth interviews, observation, and documentation, then analyzed through data reduction, data presentation, and conclusion drawing. The results showed that adolescent involvement in online gambling in Kotasan Village, Galang District, is relatively high, especially among those who have dropped out of school or are unemployed. They generally access online slot and lottery applications via smartphones, often playing in coffee shops or areas with free Wi-Fi, with the most significant influence coming from peer encouragement and easy access to technology. The impacts are evident in changes in social behavior (becoming withdrawn, lying, neglecting responsibilities), family conflicts due to misuse of money, decreased school performance or work motivation, and psychological problems such as stress and mild depression. Preventive efforts undertaken by families, community leaders, and religious institutions are still limited to advice, reprimands, or spiritual activities. However, they fail to address the root of the problem and are inconsistent. These findings confirm that online gambling poses a serious threat to adolescent development and social order, necessitating a more comprehensive prevention strategy through synergy between families, communities, religious leaders, and village governments, focusing on supervision, digital literacy, and the provision of productive activities.